ANALISIS KESALAHAN SISWA SMP DALAM MENYELESAIKAN MASALAH BANGUN RUANG BERDASARKAN TEORI PEMROSESAN INFORMASI - Latifahtul Islamiyah; Wharyanti Ika Purwaningsih; Puji Nugraheni (Universitas Muhammadiyah Semarang, 2021)
The purpose of this study was to describe the mistakes made by students in class VIII SMPN 22 Purworejo in solving the problem of building a flat side space based on information processing theory. This type of research is descriptive qualitative research. The subjects of this research were 3 students taken from 5 students of class VIIIB SMPN 22 Purworejo. The results showed that students' errors based on the information processing stages were found in the retieval stage. rehearsal and encoding. Errors in the retrieval stage include (1) errors in the use of arithmetic operations; (2) errors in the use of formulas. errors in the rehearsal stage, namely the repetition of concepts or values that are wrong and errors in the encoding stage, namely students do not re-check every answer produced.